Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1080/21505594.2023.2237222
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2: the missing piece in the puzzle of pathogen-induced damage

Abstract: Annexin A2 is a Ca 2+ regulated protein belonging to the Annexin family and is found in the cytoplasm and cell membrane. It can exist in a monomeric form or in a heterotetrameric form with the S100A10 dimer. The research on Annexin A2 in tumours is currently active, and studies on its role in pathogen infection are increasing. Annexin A2 plays a crucial role in the life cycle of viruses by mediating adhesion, internalization, uncoating, transport, and release. In the case of parasites, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 113 publications
0
1
0
Order By: Relevance
“…Moreover, our study shows that the presence of As during S. aureus infection of MAC-T cells resulted in prevention of bacterial adhesion rather than bacterial killing. Previously, it has been shown that AnxA2 can interact with a bacterial receptor, mediating the adhesion to the host cells and ultimately promoting host infection [ 34 ]. It was confirmed further that by neutralising AnxA2, Pseudomonas aeruginosa infection of mammalian cells was prevented [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our study shows that the presence of As during S. aureus infection of MAC-T cells resulted in prevention of bacterial adhesion rather than bacterial killing. Previously, it has been shown that AnxA2 can interact with a bacterial receptor, mediating the adhesion to the host cells and ultimately promoting host infection [ 34 ]. It was confirmed further that by neutralising AnxA2, Pseudomonas aeruginosa infection of mammalian cells was prevented [ 35 ].…”
Section: Discussionmentioning
confidence: 99%